eScore: An MVP for Solving the Page Turning Problem in Musical Scores - Aires, Brandow Buenos; Aleixo, Rafael Soares; Basso, Fabio Paulo; Bernardino, Maicon (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2025.14355, 2025)
Musical scores remain essential in musical practice, yet manual page-turning can disrupt the flow and quality of collaborative performances. This paper presents eScore, a solution that automatically synchronizes digital scores between musicians and conductors to eliminate interruptions and enhance performance dynamics. Developed and evaluated in real-world scenarios, eScore proved effective in reducing disruptions, fostering integration, comfort, and focus among performers. Identified improvements include interface refinement and broader device compatibility. Overall, eScore emerges as an innovative and promising tool to modernize musical practice, offering meaningful advances in collaboration and group performance efficiency.